Adaptive Evolution of Sphingobium hydrophobicum C1T in Electronic Waste Contaminated River Sediment - Song, Da; Chen, Xingjuan; Xu, Meiying; Hai, Rong; Zhou, Aifen; Tian, Renmao; Van Nostrand, Joy D.; Kempher, Megan L.; Guo, Jun; Sun, Guoping; Zhou, Jizhong (Frontiers in Microbiology, 2019)
Electronic waste (e-waste) has caused a severe worldwide pollution problem. Despite increasing isolation of degradative microorganisms from e-waste contaminated environments, the mechanisms underlying their adaptive evolution in such habitats remain unclear. Sphingomonads generally have xenobiotic-degrading ability and may play important roles in bioremediation. Sphingobium hydrophobicum C1T, characterized with superior cell surface hydrophobicity, was recently isolated from e-waste contaminated river sediment. To dissect the mechanisms driving its adaptive evolution, we evaluated its stress resistance, sequenced its genome and performed comparative genomic analysis with 19 other Sphingobium strains. Strain C1T can feed on several kinds of e-waste-derived xenobiotics, exhibits a great resistance to heavy metals and possesses a high colonization ability. It harbors abundant genes involved in environmental adaptation, some of which are intrinsic prior to experiencing e-waste contamination. The extensive genomic variations between strain C1T and other Sphingobium strains, numerous C1T-unique genes, massive mobile elements and frequent genome rearrangements reflect a high genome plasticity. Positive selection, gene duplication, and especially horizontal gene transfer drive the adaptive evolution of strain C1T. Moreover, presence of type IV secretion systems may allow strain C1T to be a source of beneficial genes for surrounding microorganisms. This study provides new insights into the adaptive evolution of sphingomonads, and potentially guides bioremediation strategies.